Reforma del art. 195.2 inciso séptimo del código del trabajo, en relación que en sentencia del despedido ineficaz se admite el recurso de apelación con efecto devolutivo, vulnerando al trabajador que presente el recurso por negativa a su pretensión - Velasteguí Marín, Daniel Eliceo (2017)
Art. 195.1 of the Labour Code prohibits the dismissal and ineffective declaration, when the person has been fired unexpectedly, this is accepted for working in pregnant or condition associated with their pregnancy or maternity, subject to the principle of tenure that protects them. Art. 195.2 of the Labour Code indicates the procedure to be taken into account in the present action dismissal ineffective, regulation that gives the guidelines should take into account the judge and the parties. But in his seventh paragraph it provides that judgments that supports ineffectiveness admissible the appeal with devolutive effect, therefore, only employers may lodge an appeal, when the trial judge considers dismissal tested. In the case of a worker who has received no to your claim, you can not bring the action, which violates the guarantees of due process, such as the right to defense stated in Article 76 paragraph 7 of the Constitution of the Republic of Ecuador , literal a) that it is deprived of the right to defense at this stage or degree of process; and c) be heard in a timely manner and on an equal footing. This causes legal uncertainty because this rule is not prior, clear, public and applicable competent authority.